Hurricane Katrina and the Burdens of History - Rothman, Adam (History compass, 2006)
Almost three months after Hurricane Katrina made landfall on the Gulf Coast, a New York Times editorial mourns, "We are about to lose New Orleans." The city remains crippled. Whole neighborhoods have been reduced to rubble. The federal, state, and local governments dither. Basic services are yet to be fully restored. Only a fraction of its residents have returned, and many never will. By the last count, more than a thousand New Orleanians died in the disaster. The sad truth is that we have already lost New Orleans. Whatever replaces it will not be the same. The city is history.1